Newly identified single-nucleotide polymorphism associated with the transition from nonalcoholic fatty liver disease to liver fibrosis: results from a nested case-control study in the UK biobank - Yitong Ling; Yu Xuan Yang; Yan Chun Chen; Jing Hao Wang; Dong Ge Feng; Shi Jian Xiang; Xiaoyu Zhang; Jun Lyu; Sha Sha Li (Annals of Medicine)
Background Genetic factors may have a significant influence on the likelihood of liver fibrosis in individuals with nonalcoholic fatty liver disease (NAFLD). The present study was conducted to explore how single-nucleotide polymorphism (SNP) impacts the development of fibrosis in those suffering from NAFLD.Materials and methods Utilizing the UK Biobank dataset, we conducted a nested case-control analysis among NAFLD participants, defining the case group as those with liver fibrosis and cirrhosis during follow-up. For our in vitro investigations, we employed the LX-2 human hepatic stellate cell line. Our procedures included cultivating these cells, employing SAMM50-rs2073080 plasmid techniques to enhance the expression of recently discovered SNPs, and conducting biochemical assays. To quantify gene expression, we used real-time PCR with fluorescence detection.Results The study analyzed data from 5467 participants (1094 cases and 4373 controls). Genome-wide association analysis identified nine significant loci, including the novel rs2073080 variant, strongly associated with NAFLD-associated hepatic fibrosis. In vitro TGF-β modeling revealed significant upregulation of α-SMA and COL1A1, confirming model effectiveness. Oxidative stress markers like elevated malondialdehyde (MDA) and reduced catalase (CAT) and superoxide dismutase (SOD) levels indicated liver damage in the TGF-β group. SAMM50-rs2073080 was upregulated in the NAFLD-associated fibrosis model. In vitro experiments on LX-2 cells showed that SAMM50-rs2073080 overexpression led to increased fibrosis, as indicated by higher cellular MDA levels and lower CAT and SOD levels, compared to the vector group.Conclusion Our research highlights a significant association of SAMM50-rs2073080 with the progression of NAFLD to hepatic fibrosis, and the in vitro experiments further corroborated these findings.